First in situ calcite U–Pb dating revealing the past episodes of the 2019 Le Teil Earthquake (France) - Gébelin, Aude; Matonti, Christophe; Larroque, Christophe; Carr, Patrick; Ampuero, Jean-Paul (Comptes Rendus. Géoscience)
In the Rhône Valley near the city of Montélimar, a Mw 4.9 surface-rupturing earthquake occurring on the 11th of November 2019 was linked to the reactivation of the NE–SW trending normal La Rouvière fault as a reverse fault mechanism. Here, we present the first in situ calcite U–Pb data acquired on well-characterized microstructures from core samples from a first exploratory drilling conducted in the NE part of the La Rouvière fault. In agreement with relative chronology data based on microstructural observations, our results allow us to define four main tectonic events: A first event from ~90 to 75 interpreted to reflect a thermal subsidence at the regional scale (Ardèche—South-East basin of France), a second event bracketed between ~60 to 50 Ma related to the N–S trending shortening of the South-East basin, a third tectonic event dated from ~40 to 37 Ma that we interpret to reflect the opening of the Gulf of Lion and European Cenozoic Rift System (ECRIS), and a fourth and final event at ~25 Ma that very likely represents a middle to late stage of the ECRIS. No more recent event has been identified on this fault.